Neotypification of Larus cachinnans Pallas, 1811 (Aves: Laridae) - Mlíkovský, Jiří; Loskot, Vladimir M. (Zootaxa, 2013)
The systematics of large white-headed gulls of the Larus fuscus-argentatus complex has long been problematic (e.g. Bruch 1853, 1855; Dresser 1873; Hartert 1921; Dwight 1925; Štegman 1934; Geyr von Schweppenburg 1938; Voous 1959) and is still in flux (e.g. Wink et al. 1994; Klein & Buchheim 1997; Panov & Monzikov 1999; de Knijff et al. 2001; Yésou 2002; Crochet et al. 2002, 2003; Liebers et al. 2004; Gay et al. 2007; Sternkopf et al. 2010). The earliest name for any Asian form is Larus cachinnans, proposed by Pallas (1811b: 318). This name is now generally applied to large white-headed gulls breeding in the Caspian region, but, as we show below, there is nothing in Pallas’s (1811b) description of the taxon that unambiguously links it with southern Palearctic forms, even less with any particular one of them (see below for the type series).